Архітектура системи вибору навчальних дисциплін студентами - Жежнич, Павло; Квятковський, Богдан; Чирка, Олег (Видавництво Наукового товариства ім. Шевченка, 2016)
This paper considers some peculiarities of students’ curriculums forming with a Virtual Student’s Cabinet. Lviv Polytechnic National University has developed the system of studying course selection by student that consists of the following components: database “University”, local functions and local users, Web-site of Virtual Student’s Cabinet.
Keywords: studying; student’s curriculum; course selection; information system; Web-system